Research on Flood Propagation for Different Dam Failure Modes: A Case Study in Shenzhen, China - Wang, Weiqi; Chen, Wenjie; Huang, Guoru (Frontiers in Earth Science, 2020)
Dam-break flood simulation can evaluate the impact of a dam break, and is significant in conducting risk analyses, creating emergency plans, and mitigating calamities. In this study, the dam-break flood evolution process in the downstream areas of Minzhi Reservoir in Shenzhen, China, was investigated using a two-dimensional shallow-water model. The two-dimensional shallow-water model was utilized for solving two-dimensional shallow water equations for free-surface flow using the finite volume method. A refined grid with an unstructured mesh of triangular cells constrained by building walls was constructed in this model to represent urban structures. The dam-break flood hydrograph and the process of the expansion of the flood under different failure conditions were determined by adopting two breach mechanisms, namely, the instantaneous and gradual dam break mechanisms. The results indicated that the peak flow of the instantaneous dam break was relatively large at the beginning of the dam break. The peak flow in the case of the gradual dam break was comparatively small when seepage failure deformation occurred near the upper part of the dam. The inundation information obtained during the evolution of the dam-break flood, including information regarding the regularity of the flood evolution, distribution of the maximum water depth, and variation of the depth and velocity with time, were also analyzed.